Leucocyte Platelet Rich Fibrin with Autologous Gingival Fibroblasts in the Treatment of Adjacent Recession Defects (2019)
ABSTRACT: Periodontium can submit changes that lead to loss of integrity, such as periodontal disease, immune disorders or traumatic brushing. One of the most common consequences resulting from these events is the apical migration of gingival marginal tissue. Among biomaterials used for periodontal tissue regeneration, fibrin matrices have received significant attention to correct gingival recessions. Five oral mucosa biopsies were extracted, fibroblasts were in vitro cultured and frozen in liquid nitrogen. Three 10 mL glass sterile tubes were filled with patient blood and centrifuged immediately; clots were extracted and compressed to obtain L-PRF membranes. Autologous oral mucosa fibroblasts were added to the membranes and surgical procedures were performed in five patients. L-PRF fibrin network pore size was too small to allow human fibroblasts penetration but they were firmly attached to membrane surface. Gingival fibroblasts from fresh cell culture and recently thawed were used to attach on the L-PRF membranes. It was possible to establish a protocol for blood collection, centrifugation, fibrin clot compression, fibroblast adhesion to the membrane surface and patient application in a relatively short time (1 hour-1 hour and 30 minutes). Two patients expressed pain symptoms and the other ones presented light swelling without pain. In the first week, adjacent tissue showed few inflammation signs. Research efforts are being conducted to develop more conservative surgical techniques and new biomaterials that can promote cellular proliferation. Because of its properties, L-PRF membranes represent a tempting alternative. A combined technique to treat adjacent recession defects with L-PRF membranes and autologous oral mucosa fibroblasts in a coronal displaced flap did not show initial advantage compared with a gold standard surgery that includes an autologous soft tissue graft. Nevertheless, it could be an alternative for clinical application as a new functional cell biomaterial. More clinical evidence is needed.